2014
DOI: 10.1093/ejcts/ezu290
|View full text |Cite
|
Sign up to set email alerts
|

The German Aortic Valve Registry: 1-year results from 13 680 patients with aortic valve disease†

Abstract: Conventional AVR surgery yields excellent results after 1 year in lower-risk patients. Catheter-based AVR is a good alternative in high-risk and elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
81
3
6

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 161 publications
(98 citation statements)
references
References 24 publications
8
81
3
6
Order By: Relevance
“…[8][9][10][11][12][13][14][15] In Japan, reimbursement of TAVI was approved in October 2013. However, only limited data on TAVI are currently available, and its efficacy and safety in Japanese patients have not yet been sufficiently investigated.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15] In Japan, reimbursement of TAVI was approved in October 2013. However, only limited data on TAVI are currently available, and its efficacy and safety in Japanese patients have not yet been sufficiently investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The mean patient age in the TAVI group was 81.5 years, and the STS score was 5.8% in each group. This study showed no differences in the rate of a combined endpoint that included allcause mortality and stroke [15]. In patients treated using the femoral approach, a statistically significant lower rate of the combined endpoint was shown compared to surgical treatment (HR = 0.79, p = 0.05, intentiontotreat) [7].…”
Section: Intermediate-risk Patientsmentioning
confidence: 49%
“…The prospective German GARY registry showed compa rable mortality with SAVR and TAVI in higherrisk groups but lower mortality with SAVR in lowrisk groups [15].…”
Section: Low-risk Patientsmentioning
confidence: 97%
“…Two-year mortality and stroke rates were comparable in the two treatment arms (9.8% vs. 8.0%, p = 0.54 and 5.4% vs. 3.6%, p = 0.46, respectively) [33,34]. With these results in mind, data of the prospective German GARY registry observed a comparable mortality in high-risk patients undergoing SAVR and TAVI, while a lower mortality was reported in SAVR vs. TAVI in low-risk patient groups [31].…”
Section: Tavi In Low-risk Patientsmentioning
confidence: 75%
“…The mean age was 81 years, and STS was 5.8% in each group. The composite endpoint (all-cause mortality and stroke) did not differ between SAVR and TAVI [31]. In the transfemoral TAVI group, the risk of composite endpoint occurrence was significantly smaller in comparison to the SAVR group (HR = 0.79, p = 0.05, intention-to-treat) [7].…”
Section: Tavi In Intermediate Risk Patientsmentioning
confidence: 83%